Importance of Skin Changes in the Differential Diagnosis of Congenital Muscular Dystrophies. (31st March 2016) - Yis, Uluç; Baydan, Figen; Karakaya, Mert; Hız Kurul, Semra; Cirak, Sebahattin
Abstract : Megaconial congenital muscular dystrophy (OMIM 602541) is characterized with early-onset hypotonia, muscle wasting, proximal weakness, cardiomyopathy, mildly elevated serum creatine kinase (CK) levels, and mild-to-moderate intellectual disability. We report two siblings in a consanguineous family admitted for psychomotor delay. Physical examination revealed proximal muscle weakness, contractures in the knee of elder sibling, diffuse mild generalized muscle atrophy, and dry skin with ichthyosis together with multiple nummular eczema in both siblings. Serum CK values were elevated up to 500 U/L. For genetic work-up, we performed whole exome sequencing (WES) after Nimblegen enrichment on the Illumina platform. The WES revealed a novel homozygous missense mutation in the Choline Kinase-Beta ( CHKB ) gene c.1031G>A (p.R344Q) in exon 9. Ichthyosis-like skin changes with intense pruritus and nummular eczema may lead to clinical diagnosis in cases with megaconial congenital muscular dystrophy.